Principle of entrepreneurship (ENT530): business model canvas: YHijabs / Siti Nur Hidayah Mucha - Mucha, Siti Nur Hidayah (2020)
YHijabs provide variety type and colours of hijab for the customers such as shawl, scarf and more. Our priorities for our company are customers’ satisfaction and the quality of products that we have. Our target customer is more to residences in Kuching as our location at residence area. Our products are suitable for any ages whether from children to adults in the location. Meanwhile our price of the products also affordable for our customers. To be acknowledge by the customers, we use 4P strategies which is promotion, product, price and place strategy. We sure that by using this 4P strategies, we can gain our products profit like we planned before and compete with other competitors. This business is in the form of partnership which are consist of two members which are Miss Siti Nur Hidayah, and Miss Melor. We hope that with all the commitment we have from each of us, we can achieve our company mission which is to become success and well-known in Sarawak as well in Malaysia.